Efektivitas Sosialisasi Bank Muamalat KCP Parepare Terhadap Peningkatan Minat Menabung Masyarakat - Sri Wahyuni. A, Andi Bahri, S, Musmulyadi, Moh. Yasin Soumena, Zulkarnain, Safrida (STIE AMKOP, 2023)
Bank socialization is one form of the Bank's work program in increasing people's interest in saving. Socialization plays an important role in introducing the Sharia Banking system to the public, because there are still many people who only know Sharia Banks from their skin so they think that the Sharia Banking system is the same as Conventional Bank system. The aim of this research is to determine the form of socialization of Bank Muamalat KCP Parepare and how to increase people's interest in saving at Bank Muamalat KCP Parepare. This research uses a qualitative descriptive research method and is a type of field research. The results of the research show that 1) the form of socialization carried out by the Bank is socialization in various agencies and non-agencies by offering various products at Bank Muamalat, but the community hopes that the Bank will reach more people so that they can flock to use the services of Sharia Bank. 2) increased interest after the socialization was carried out, on average informants who had taken part in the socialization have now become customers and use Bank Muamalat's services in all matters of their financial institutions, as stated by the bank, the number of customers has increased by 50-60 people per month, while Bank Muamalat's target per month is an additional 50 customers. people then the increase in people's interest in saving increases after participating in the socialization.